Bibliometric Analysis Online Marketplace Analysis - Asyahuri, Sofiyan; Setiawan, Adi; Syifaudin, Syifaudin (International Journal of Engineering, Science and Information Technology, 2025)
Online marketplaces have revolutionized the world of modern commerce by offering a digital platform that enables transactions without the need for individual website management. This study aims to analyze the influence of marketplaces on consumer behaviour, business strategies, and digital economic transformation. The study uses a qualitative approach with a historical analysis method, examining 1,230 scholarly articles published between 1961 and 2024. The results show that factors such as big data, social media, and consumer personalization play an essential role in the success of marketplaces. However, key challenges include competition in the market, customer data management, and logistical constraints, all of which require continuous innovation. Through network visualization, opportunities for further research on subthemes, such as "customer experience" and "new economy," were identified. "This study provides strategic insights that can improve the efficiency and competitiveness of marketplaces in the global digital ecosystem.